Selective increase of Nurr1 mRNA expression in mesencephalic dopaminergic neurons of D2 dopamine receptor-deficient mice - Tseng, Kuei y (2000)
The orphan nuclear receptor Nurr1 is critical for the survival of mesencephalic dopaminergic precursor neurons. Little is known about the mechanisms that regulate Nurr1 expression in vivo. Other members of this receptor family have been shown to be activated by dopamine. We sought to determine if Nurr1 expression is also regulated by endogenous dopamine through dopamine receptors. Consequently, we investigated the expression of Nurr1 mRNA in genetically modified mice lacking both functional copies of the D2 dopamine receptor gene and in their congenic siblings. Quantitative in situ hybridization demonstrated a significant increased expression of Nurr1 mRNA in the substantia nigra pars compacta and the ventral tegmental area of D2 dopamine receptor -/- mice. No change in Nurr1 expression was detected in other brain regions, such as the habenular nuclei and temporal cortex. Among the cell groups studied, mesencephalic dopaminergic neurons are unique in that they express both Nurr1 and the D2 dopamine receptor, and synthesize dopamine. Thus, it seems plausible that the selective increase in Nurr1 expression observed in D2 receptor-deficient mice is the consequence of an impaired dopamine autoreceptor function. Copyright (C) 2000 Elsevier Science B.V.